Physical activity and exercise as countermeasures to physical frailty and sarcopenia - Marzetti, Emanuele; Calvani, Riccardo; Tosato, Matteo; Cesari, Matteo; Di Bari, Mauro; Cherubini, Antonio; Broccatelli, Marianna; Savera, Giulia; D’Elia, Mariaelena; Pahor, Marco; Bernabei, Roberto; Landi, Francesco (Aging clinical and experimental research, 2017)
The identification of cost-effective interventions that improve the health status and prevent disability in old age is one of the most important public health challenges. Regular physical activity is the only intervention that has consistently been shown to improve functional health and energy balance and to reduce the risk of cardiovascular disease, stroke, diabetes, several cancers, depression and falls. In advanced age, physical activity is also effective at mitigating sarcopenia, restoring robustness, and preventing/delaying the development of disability. On the other hand, physical inactivity is recognized as one of the leading causes of several chronic degenerative diseases and is also a major contributing factor to sarcopenia and functional disability. This compelling evidence has prompted the World Health Organization to recommend engaging in regular physical activity throughout one’s life course. The present review summarizes the available evidence in support of physical activity as a remedy against physical frailty and sarcopenia. The relevant pathways through which the benefits of physical activity are conveyed are also discussed.